Papua New Guinea food price bulletin: December 2020 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2021)
Prices of major food staples in Kokopo, Lae and Port Moresby have remained broadly stable over 2019 and 2020. The exceptions are prices of sweet potatoes and cooking bananas in Port Moresby, which declined between mid-2019 and the third quarter of 2020. Per kilogram prices of vitamin-dense foods such as broccoli, carrot and karakap are typically higher than prices of starchy staples. Prices of both carrots and broccoli in Lae rose in mid-2020, but have declined in the last quarter of 2020 and October prices were close to their price levels in late 2019. More consistent and timely price data collection and database management is necessary for informative food market analysis. Price data reported in this bulletin by crop and market is limited to 10 observations (at most) out of a possible of 24 fortnights in 2019. The rate of price data reporting has been lower in 2020, in part due to Covid-19 related disruptions.